ANALISIS FAKTOR – FAKTOR YANG MEMPENGARUHI MINAT BERWIRAUSAHA MAHASISWA S1 MANAJEMEN FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS MATARAM - I GUSTI AGUNG ARISTA PRADNYANI; DEWI RISPAWATI; NILA RAHAYU; TONY WINATA (Universitas Mahasaraswati K. Mataram, 2024)
An important component of a country's economic success is entrepreneurship. Therefore, the government tries to encourage people to start their own businesses by offering loans, support, and entrepreneurship education. This study is very important to conduct because knowing the entrepreneurial interest of students and the factors that influence it can be a source of reference and can contribute to the development of studies on entrepreneurship which is very important to be encouraged today. The purpose of this study is to improve the teaching of entrepreneurship, and it may be useful for faculties to explore expanding the reach of programs that encourage students to pursue entrepreneurial endeavors. This study employed the associative quantitative technique. The study's sample comprised 92 participants who had completed an introductory course on entrepreneurship at the University of Mataram Faculty of Economics and Business. Everybody there was a student in the program for management studies. The study's conclusions suggest that entrepreneurship education influences people's aspirations to launch their own companies. Personality has no bearing on one's ambition to start their own business. Motivation influences a person's interest in starting their own business. The home environment influences a person's interest in business. Both the social milieu and the aspiration to pursue entrepreneurship bear significance.